The Challenges of the “Divided” Heritage of Cyprus - Grchev, Kokan; Dinçyürek, Özgür (Springer, 2019)
By opening the issues of “divided” heritage of Cyprus, this study intends to discuss different continuities as well as internationally established consensuses on cultural heritage and its identity. Heritage is discussed as representing and evolving contemporary culture, problematizing human existence and guiding the future of the societies and cultures towards valuable identities. Perceived heritage of the island as a specific resource is questioned theoretically and by following the activities of the “Technical Committee on Cultural Heritage in Cyprus”, in their efforts to bring together some practices aimed for heritage positioning in the focus of contemporary culture. Specific discourse is open towards the evident need of monuments on one side, and the social integration of heritage in cultural and development activities on the other. Unique emergencies are recognized as challenging the existence of both. © 2019, Springer Nature Switzerland AG.
Keywords: Challenges; Cultural heritage; Emergencies; Identity; Monuments